2007
DOI: 10.1128/mcb.00018-07
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Histone H3 Phosphorylation by Vaccinia-Related Kinase 1 in Mammalian Cells

Abstract: Mitotic chromatin condensation is essential for cell division in eukaryotes. Posttranslational modification of the N-terminal tail of histone proteins, particularly by phosphorylation by mitotic histone kinases, may facilitate this process. In mammals, aurora B is believed to be the mitotic histone H3 Ser10 kinase; however, it is not sufficient to phosphorylate H3 Ser10 with aurora B alone. We show that histone H3 is phosphorylated by vaccinia-related kinase 1 (VRK1). Direct phosphorylation of Thr3 and Ser10 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
195
1
34

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(244 citation statements)
references
References 48 publications
(85 reference statements)
14
195
1
34
Order By: Relevance
“…This augmentation remains unexplained; although it is possible that the over accumulation of p105HEF1 might result in increased phosphorylation. Alternatively, there are examples of proteins in which a single residue is the target of different kinases [41,42]. So we can not exclude that other kinase(s) phosphorylate HEF1 on ser-369 but also on another residue leading to an HEF1 isoform that would be less sensitive to degradation and would be part of the p115 band.…”
Section: Discussionmentioning
confidence: 97%
“…This augmentation remains unexplained; although it is possible that the over accumulation of p105HEF1 might result in increased phosphorylation. Alternatively, there are examples of proteins in which a single residue is the target of different kinases [41,42]. So we can not exclude that other kinase(s) phosphorylate HEF1 on ser-369 but also on another residue leading to an HEF1 isoform that would be less sensitive to degradation and would be part of the p115 band.…”
Section: Discussionmentioning
confidence: 97%
“…In metazoa, H3T11 is likely phosphorylated by the Dlk/ZIP kinase, 15 a member of the death associated protein kinase family that lacks true orthologs in plants. 16 H3T3 and H3S10 also seem to be phosphorylated by Vaccinia-Related Kinase 1 (VRK1), 17 another metazoa-specific protein (Fig. 1).…”
Section: Histone H3 Phosphorylation During Mitosismentioning
confidence: 99%
“…14,18,19 This pattern of phosphorylation and other analyses suggested that H3S10ph and H3S28ph might play a role in chromosome condensation. 8,17,20 Phosphorylation of H3T3 initially overlaps with that of H3S10ph but, at metaphase, H3T3ph is more intensely concentrated in the central region of the metaphase plate. 14,19 In metazoa, H3T3ph has been implicated in metaphase chromosome alignment and centromeric cohesion, 8,14 although given the similarities with the H3S10ph distribution, it might also function in chromosome condensation.…”
Section: Histone H3 Phosphorylation During Mitosismentioning
confidence: 99%
“…VRK1, the most abundant Ser-Thr kinase in nuclei [23], is a nucleosomal/chromatin kinase that can form complexes and phosphorylate several transcription factors [24][25][26], histones [18,[27][28][29] and other chromatin proteins [30,31]. Moreover, VRK1 kinase activity can also be regulated by these proteins interactions, including those with histones [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…VRK1 is required for G0 exit, behaving like an early gene such as MYC and FOS [36]. VRK1 is also required for phosphorylation of histone H3 and chromatin compaction late in mitosis [27]. Moreover, VRK1 positively correlates with the proliferation phenotype in human head and neck [37] and lung cancers [34,38], and in breast cancer xenographs it also affects proliferation [39].…”
Section: Introductionmentioning
confidence: 99%